PENGARUH SISTEM PENGENDALIAN INTERNAL DAN TEMUAN KEPATUHAN TERHADAP OPINI AUDIT PADA PEMERINTAH DAERAH - Safitri, Ni Luh Ketut Shanti Antik; Darsono, Darsono (Diponegoro Journal of Accounting, 2015)
The aims of this research are to examine the effect of internal control weaknesses and the number of audit compliance findings on audit opinion in public sector. Prior research, Kawedar (2010), and Sipahutar and Khairani (2013) discovered that the decreasing of internal control weaknesses and the number of audit compliance findings affect the audit opinion given by the audior.This research tested 354 regional financial statements in the area of Java from 2010 until 2012. Area sampling design method was used to select the financial statements. This research used logistic regression for data analysis and hypothesis examination. The result of the study indicated that internal control weaknesses and budget realization is not significant to the audit opinion. Otherwise, audit compliance findings have negative influence to audit opinion.